2020
DOI: 10.3390/molecules25235606
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Properties and Phenolic Compound Profiles of Turnip-Rooted, Plain-Leafed and Curly-Leafed Parsley Cultivars

Abstract: Petroselinum crispum Mill., Fuss., is a culinary vegetable used as an aromatic herb that garnishes and flavours a great variety of dishes. In the present study, the chemical profiles and bioactivities of leaf samples from 25 cultivars (three types: plain- and curly-leafed and turnip-rooted) from this species were assessed. Seven phenolic compounds were identified in all the varieties, including apigenin and kaempherol derivates. Apigenin-O-pentoside-O-hexoside was the major compound in all the tested parsley t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 47 publications
(68 reference statements)
3
26
0
1
Order By: Relevance
“…They feature high antioxidant activity linked to the content of vitamin C, carotenoids, phenolics, and other antioxidants [Boggia et al, 2015;Pérez-Gálvez et al, 2020;Śledź et al, 2013]. Currently, there is a lot of interest in their potential use as ingredients in functional foods, which is due to the high content of natural antioxidants (including phenolics) and essential oils [Ahmed et al, 2019;Liberal et al, 2020]. Certain compounds present in basil, especially quercetin and ursolic acid, have been proved to inhibit the formation of nitric oxide II -an inflammatory factor mediating cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…They feature high antioxidant activity linked to the content of vitamin C, carotenoids, phenolics, and other antioxidants [Boggia et al, 2015;Pérez-Gálvez et al, 2020;Śledź et al, 2013]. Currently, there is a lot of interest in their potential use as ingredients in functional foods, which is due to the high content of natural antioxidants (including phenolics) and essential oils [Ahmed et al, 2019;Liberal et al, 2020]. Certain compounds present in basil, especially quercetin and ursolic acid, have been proved to inhibit the formation of nitric oxide II -an inflammatory factor mediating cancer development.…”
Section: Introductionmentioning
confidence: 99%
“…Research findings are indicate that BM, chard, and parsley have a strong antioxidant activity and their phenolic content may be associated with the antioxidant activity (Kubola & Siriamornpun, 2008; Liberal et al, 2020; Sacan & Yanardag, 2010). Moreover, it has been reported that BM, chard, and parsley improve antioxidant defense and suppress oxidative stress in various tissues (Gezginci‐Oktayoglu et al, 2014; Maodaa et al, 2016; Thenmozhi & Subramanian, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Eva Ivanišová 1 *, Miroslava Kačániová 2 , Tatsiana A. Savitskaya 3 and Dmitry D. Grinshpan 4 1 Faculty of Biotechnology and Food Sciences, Slovak University of Agriculture in Nitra, Nitra, Slovakia…”
Section: Author Detailsmentioning
confidence: 99%
“…These compounds are well known for their biological activity such as anticancer, antioxidant, antimicrobial, neuroprotective, antidiabetic, cardio protective and many others positive effect to human body. It is important to determine their safe intake and dosage in health, gastronomy and food industry [3,4].…”
Section: Introductionmentioning
confidence: 99%